2014
DOI: 10.14202/vetworld.2014.1047-1057
|View full text |Cite
|
Sign up to set email alerts
|

Effect of balanced concentrate ration on the performance and hematobiochemical profile of lactating native ewes and lambs in coastal Odisha

Abstract: Aim: The present study was conducted to evaluate the effect of supplementation of balanced concentrate ration during lactation on the growth performance, blood and metabolic profiles of native ewes and lambs in coastal Odisha. Materials and Methods:A total of 40 numbers of lactating ewes of the same parity comprised the experimental animals. The selected ewes were randomly assigned to two groups of twenty each, maintaining uniformity in body weight (13.36±0.33 kg for Group 1 and 13.48±0.37 kg for Group 2). Gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Runa et al (2022) showed no effect of age on transaminase activity in Black Bengal goats. This discrepancy in results could be attributed to the variations in the breed (Hajinejad-Bamroud et al, 2020), surroundings, dietary intake, and overall health condition of the animals (Beura et al, 2014).…”
Section: Age and Liver Parametersmentioning
confidence: 95%
“…Runa et al (2022) showed no effect of age on transaminase activity in Black Bengal goats. This discrepancy in results could be attributed to the variations in the breed (Hajinejad-Bamroud et al, 2020), surroundings, dietary intake, and overall health condition of the animals (Beura et al, 2014).…”
Section: Age and Liver Parametersmentioning
confidence: 95%
“…Ruminants including sheep have the unique ability to survive harsh environmental conditions and food shortages. For this reason, they are the preferred rearing animals in arid, semi-arid and dry hilly areas and are of central economic importance for most people of these areas [2,4]. The estimated population of sheep in Pakistan is 31.9 million heads; they are reared for mutton, wool, milk and hide production.…”
Section: Introductionmentioning
confidence: 99%